British union-catalogue of periodicals : incorporating world list of scientific periodicals - Gascoigne J.; Porter, Kenneth I. (Butterworths, 1977)
"The British union-catalogue of periodicals (BUCOP) in its new form is concerned with the recording of new periodical titles for the period in and after 1960."
Edited 1964-69 by K.I. Porter
Keywords: Periodicals -- Bibliography -- Union lists